2012
DOI: 10.1155/2012/813920
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Quality and Attitudes toward Mathematics: Do Self-Concept and Interest Differ across Students' Patterns of Perceived Instructional Quality in Mathematics Classrooms?

Abstract: Using a person-centered research approach, the present study explored individual differences in students' perceptions of instructional quality in secondary school mathematics classes and their relations to students' self-concept and interest in mathematics. Drawing on data collected from 425 high school students from ten schools in Berlin, Germany (male: 53.2%; female: 46.3%), latent class analyses (LCA) revealed four distinct patterns of perceived quality of instruction. Almost half of the sample (46%) had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Research shows that instructions or feedback, similar to marks, influence pupil self-concept and thereby motivation to study and form part of the learning process (cf. Lazarides and Ittel 2012;Wentzel et al 2010).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Research shows that instructions or feedback, similar to marks, influence pupil self-concept and thereby motivation to study and form part of the learning process (cf. Lazarides and Ittel 2012;Wentzel et al 2010).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Gender served as another student-level covariate, because some research has suggested that gender differences may exist in student ratings for both achievement motivation and instructional quality (Lazarides and Ittel 2012;Meece et al 2006a, b;Wigfield et al 2002).…”
Section: Control Variables: Gendermentioning
confidence: 99%
“…In this context, Klieme et al ( 2009 ) pointed out that a supportive climate is the strongest predictor of students' motivation and affect. Lazarides and Ittel ( 2012 ) extended the existing body of research with a study that revealed that individual students' perceptions of instructional quality were associated with their self-concept and attitudes in mathematics. Generally speaking, there is some evidence that instructional quality is related to students' educational outcomes.…”
Section: Introductionmentioning
confidence: 99%